Evaluation of Lipid Parameters in Diabetic and Non-Diabetic Acute Myocardial Infarction Patients in Al-Bayda - Fathia Hussien; Kasem Abdinibi (AlQalam Journal of Medical and Applied Sciences, 2023)
Aims. This study aimed to evaluate lipid profile in diabetic and non-diabetic acute myocardial infarction (AMI) patients. Methods. Retrospective cross-sectional analysis of clinical and laboratory data was extracted from hospital records of Al-Bayda Medical Center, recorded data for 140 subjects, divided into two groups (Non-diabetic AMI, N-AMI; and Diabetic AMI, D-AMI). Biochemical data such as fasting plasma glucose (FPG), glycated hemoglobin HbA1c, systolic and diastolic blood pressure, total cholesterol (TC), triglycerides (TG), low-density lipoprotein (LDL), high-density lipoprotein (HDL), TC/HDL, LDL/HDL ratios, and data for cardiac markers Troponin-I (TnI), C-reactive protein (CRP) along with the patient’s age and gender, were also taken from file system. Results. D-AMI individuals had high level of TC, TG, LDL, and low level of HDL in comparison to N-AMI individuals. Conclusion. The current tudy showed elevated lipid marker in D-AMI patients compared to N-AMI patients. These results will be helpful for clinicians in therapy of MI patients with DM.